Effect of photorefractive keratectomy on agreement of anterior segment variables obtained by a swept-source biometer vs a Scheimpflug-based tomographer. Issue 9 (September 2020) - Salouti, Ramin; Kamalipour, Alireza; Masihpour, Nasrin; Zamani, Mohammad; Ghoreyshi, Maryam; Salouti, Kia; Nowroozzadeh, M. Hossein
Abstract : PRK decreased the agreement between Pentacam-AXL and IOLMaster 700 for mean keratometry and J0 but not for J45, ACD, WTW distance, or AL. The LoAs for CCT became narrower after PRK, with minimal clinical relevance. Abstract : Purpose: To evaluate agreement of anterior segment variables between Pentacam-AXL and IOLMaster 700 before vs after photorefractive keratectomy (PRK). Setting: Salouti Eye Clinic, Shiraz, Iran. Design: Prospective cohort with interdevice agreement analysis. Methods: This study included healthy PRK candidates who were assessed with both devices preoperatively and 6 months after PRK. Only data from the right eye of each patient was analyzed. Pentacam-AXL average keratometry (AvgK) and zonal keratometry in the central 2.5 mm zone (zonal-K2.5) were each compared with mean keratometry (Km) from the IOLMaster 700. Other main outcome measures included vector analysis of corneal astigmatism (J0 and J45), central corneal thickness (CCT), anterior chamber depth (ACD), and white-to-white (WTW) distance. Axial length (AL) measurements by the same devices on a new cohort of 40 patients who had undergone PRK were also assessed. A paired t test was used to assess the interdevice measurement differences, and Bland-Altman analysis was used to calculate the 95% limits of agreement (LoA). Results: This study included 97 patients. Preoperative vs post-PRK 95% LoAs between Pentacam-AXL and IOLMaster 700 were as follows: AvgK/Km (−0.42, 0.08 diopter [D]) vs (−0.49, 0.18 D); zonal-K2.5/Km (−0.40, 0.32 D) vs (−0.57, 0.74 D); J0 (−0.33, 0.18 D) vs (−0.28, 0.35 D); J45 (−0.28, 0.23 D) vs (−0.24, 0.27 D); pupil pachymetry/CCT (−18, 12 μm) vs (−2.6, 19.6 μm); apical pachymetry/CCT (−17.4, 12.8 μm) vs (−1.7, 20.9 μm); ACD (−0.03, 0.13 mm) vs (−0.03, 0.13 mm); WTW (−0.68, 0.23 mm) vs (−0.63, 0.14 mm); and AL (−0.07, 0.01 mm) vs (−0.07, 0.03 mm), respectively. Conclusions: PRK showed a negative impact on interdevice agreement for CCT and corneal power measurements, whereas it did not have a significant effect on the agreement of devices for ACD, WTW, AL, and the J45 astigmatism vectoral component. For IOL power measurement in post-PRK eyes, the 2 devices could be regarded as interchangeable for measuring AL and ACD but not for keratometry readings.